The breeding ecology of the barn swallow Hirundo rustica gutturalis in South China. (10th May 2016) - Pagani-Núñez, Emilio; He, Chao; Li, Biao; Li, Ming; He, Ruchuan; Jiang, Aiwu; Goodale, Eben
Abstract: Some animal species are found in many environments and over wide distributions and may have adaptations to live in such different areas. The barn swallow Hirundo rustica is an example of a species that is able to thrive over a large geographic range and in many different environments. However, little is known of the breeding biology of this species in southern China. Here, we studied 18 breeding pairs of barn swallow H. r. gutturalis in Nanning, Guangxi, between April and July 2015. We studied its breeding fitness and parental investment. We found that tropical barn swallows bred from early April to early July and had from two to five fledglings per brood. We also recorded a strong seasonal decrease of breeding success and nestling condition that has also been found in temperate regions. Nevertheless, nestlings showed relatively long wings and low body masses, which may have enabled three sets of parents to raise three broods per breeding season, more than in other Chinese populations. Generally, barn swallows breeding in the tropics showed a similar ecology to their conspecifics from temperate regions, probably due to the species' niche specificity in urban settings. Morphological differences detected in this study require further research based on larger sample sizes and on more detailed data from different climatic regions of Asia.